Useful public health countermeasures to control the current multicountry outbreak of Monkeypox disease - Diatta, Khadija Leila El Siby; Faye, Oumar; Sall, Amadou Alpha; Faye, Ousmane; Faye, Martin (Frontiers in Public Health, 2023)
Monkeypox is a viral disease endemic to some countries in Central and Western Africa. However, sporadic human cases have also been reported outside of Africa. The first human case was reported in 1970 in the Democratic Republic of Congo. Very similar to the eradicated smallpox regarding its clinical representation, the Monkeypox disease is most common in children between 5 and 9 years old with a fatality rate ranging from 1 to 11% in Africa. During the last decade, the number of countries that reported human cases of the disease grew significantly, while experts still seek knowledge on the virus characteristics. The recent increase of Monkeypox cases in many countries raises the concern of a possible global health threat. There is a need to subsequently provide insights into the incidence of Monkeypox disease and come up with mechanisms to prevent its emergence and contain its spread. Furthermore, it is crucial to have better view on the global diagnostic capacity of Monkeypox virus. This review aims to assess useful public health countermeasures to control the current multi-country outbreak of Monkeypox disease.